Immotile Cilia Syndrome: A case Report (Medical Forum Monthly, 2024)
Immotile cilia syndrome is a genetic disorder characterized by defects in the structure and function of cilia, which are hair-like structures that protrude from the surface of cells and play a role in various physiological processes, including the movement of mucus in the respiratory tract. PCD is often autosomal recessive to manifest the disease. The impaired movement of cilia in the respiratory tract can result in the ineffective clearance of mucus and debris. This makes individuals with PCD more susceptible to respiratory infections such as sinusitis, bronchitis, and pneumonia.